Reducing child undernutrition: how far does income growth take us? - Haddad, Lawrence J.; Alderman, Harold; Appleton, Simon; Song, Lina; Yohannes, Yisehac (International Food Policy Research Institute, 2002)
How rapidly will child undernutrition respond to income growth? This study explores that question using household survey data from 12 countries. In addition, data on the undernutrition rates since the 1970s available from a cross-section of countries are employed in this investigation. Both forms of analysis yield similar results. Income increases at household and national levels imply similar rates of reduction in undernutrition. Using these estimates and better-than-historical income growth rates, we find that the Millennium Development Goal (MDG) of halving the levels of child underweight by 2015 is unlikely to be met through income growth alone. What is needed is a balanced strategy of income growth and investment in more direct interventions to accelerate reductions in undernutrition.